2020
DOI: 10.3390/ijms21072423
|View full text |Cite
|
Sign up to set email alerts
|

miR-1285-3p Controls Colorectal Cancer Proliferation and Escape from Apoptosis through DAPK2

Abstract: MicroRNAs are tiny but powerful regulators of gene expression at the post-transcriptional level. Aberrant expression of oncogenic and tumor-suppressor microRNAs has been recognized as a common feature of human cancers. Colorectal cancer represents a major clinical challenge in the developed world and the design of innovative therapeutic approaches relies on the identification of novel biological targets. Here, we perform a functional screening in colorectal cancer cells using a library of locked nucleic acid (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 44 publications
(51 reference statements)
0
9
0
Order By: Relevance
“…It is estimated that around 1 million people will be affected by CRC every year, accompanied by overt metastatic disease [2]. Recently, several methods including radiotherapy and chemoradiotherapy have been used for the treatment of CRC for years [5][6][7]. However, the prognosis of patients with CRC is still unsatisfactory [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is estimated that around 1 million people will be affected by CRC every year, accompanied by overt metastatic disease [2]. Recently, several methods including radiotherapy and chemoradiotherapy have been used for the treatment of CRC for years [5][6][7]. However, the prognosis of patients with CRC is still unsatisfactory [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several methods including radiotherapy and chemoradiotherapy have been used for the treatment of CRC for years [5][6][7]. However, the prognosis of patients with CRC is still unsatisfactory [5][6][7]. Therefore, identifying specific biomarkers is of great importance to improve early diagnosis and investigate novel treatment strategies for patients of CRC.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports presented that miR-1285-3p modulated multiple molecular targets and served as a sponge in ovarian cancer 29 , oral squamous cell carcinoma 30 , and cervical cancer 31 . Upregulated the expression of miR-1285-3p also inhibited cell proliferation and escape from apoptosis of colorectal cancer 32 . Our study confirmed that the expression level of circRNA_400029 was negatively correlated with miR-1285-3p in CC tissues and cells.…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, miR-135a promoted the proliferation and invasion of oxaliplatin-resistant gastric cancer cells, and inhibited E2F transcription factor 1 (E2F1) induced apoptosis by inhibiting E2F1 and DAPK2 expression (Yan et al, 2016b). In colorectal cancer, miR-1285-3p improved colorectal cancer cell proliferation and escape from apoptosis by targeting DAPK2 (Villanova et al, 2020). In diabetic cardiomyopathy (DCM), lncRNA myocardial infarction associated transcript (MIAT) was significantly upregulated in the rat model of DCM.…”
Section: Non-coding Rnas Involved In the Transcription Regulation Of Death-associated Protein Kinase2mentioning
confidence: 99%